Methodological instructions for completing a calculation and graphic task in the "Computer electronics" academic discipline - Skorodielov, Volodymyr Vasyliovych; Podorozhniak, Andrii Oleksiiovych; Heiko, Hennadii Viktorovych (National technical university "Kharkiv polytechnic institute", 2024)
Methodical instructions for a computational and graphic task provide for independent work in the discipline "Computer electronics", the goals of which are: to give knowledge about the element base of computers (discrete passive electronic components, semiconductor devices, microcircuits), the principles of constructing on their basis typical functional units of analog and analog-digital devices of computers and various kinds of converters in microprocessor and microcontroller systems; to provide theoretical and engineering training necessary for the development, research and operation of various analog computer devices, microprocessor and microcontroller systems, as well as specialized computer systems for various purposes; to provide practical skills in the development and analysis of computer hardware, microprocessor and microcontroller systems using modern programs for modeling electronic circuits. The performance of the computational and graphic task involves the consolidation of knowledge and the acquisition of practical skills in the construction, calculation and modeling of analog device circuits. Each student receives an individual task in accordance with its version and clarifies the initial data with the teacher. The study of the operation of circuits is carried out using programs for modeling electronic circuits. Theoretical information and reference materials that are necessary for the performance of this calculation and graphic task are given in the recommended literature and lecture materials. The execution of a computational and graphic task is considered on the examples.
Keywords: methodological instructions; microcontroller systems; voltage divider; diodes; analog-digital devices; electronic circuits